Analgesic Efficiency of Tramadol Administered Prior to Hysteroscopy Procedure - Pınar Kadiroğulları; Kerem Doğa Seçkin; Burak Yücel; Berna Aslan Çetin; Sibel Arslan Barut; Gökhan Yıldırım (Medical Network, 2016)
OBJECTIVE: In this study, our objective was to assess the pain scores using the Visual Analogue Scale (VAS) in patients who were given tramadol prior to office hysteroscopy in order to demonstrate its analgesic activity when given before this procedure. STUDY DESIGN: This prospective study conducted in year 2015 included two group of patients undergoing office hysteroscopy that were defined on the basis of the type of analgesia. Patients in the first group (Group 1, n=44) received oral tramadol prior to the procedure, while patients in the other group (Group 2, n=44) received placebo. VAS scores were determined during (0 minutes) and after (15 minutes) the procedure. RESULTS: There were no significant differences between groups in terms of age, parity and body mass index (p>0.05). Comparison of VAS scores at 0 and 15 minutes, lower values were observed in tramadol patients at 0 minutes (p<0.05), while scores at 15 minutes were not significantly different between the groups (p>0.05). CONCLUSION: Although oral tramadol given prior to office hysteroscopy was effective and safe in reducing pain during the procedure, it is not useful for the pain that occurs after processing.